Integrating Tamiang Malay Language Preservation into Local Content Curriculum: A Case Study of SMA Negeri 1 Seruway - Imam Hadi Sutrisno; Baihaqi Baihaqi; Makhroji Makhroji; Okhaifi Prasetyo (AL-ISHLAH: Jurnal Pendidikan, 2025)
The declining ability of younger generations to understand and use regional languages is a growing concern, driven by globalization and the dominance of national languages in formal education. In Pesisir Timur Aceh, the Tamiang Malay language, which plays a vital role in preserving cultural identity and transmitting local wisdom, is increasingly marginalized. This study investigates the integration of Tamiang Malay into the local content curriculum at SMA Negeri 1 Seruway as a strategy to address this linguistic decline. A qualitative descriptive method was employed, involving classroom observations, semi-structured interviews with teachers, students, and community leaders, and documentation analysis of teaching materials. Data were analyzed through reduction, categorization, and verification, with triangulation to ensure credibility. The findings reveal that Tamiang Malay integration is implemented contextually through the use of textbooks, modules, and digital media infused with cultural values. Teaching strategies emphasize communicative and experiential learning, including dialogue sessions, pantun (rhyme) competitions, and folk theater performances. These methods have improved students’ comprehension of traditional vocabulary such as sidu, leren, tibun/laboh, gemane, nyambat, and pedeh, which were previously at risk of disappearing. This study concludes that integrating regional languages into the school curriculum, supported by culturally responsive pedagogy, is an effective approach to revitalizing local language use. The initiative at SMA Negeri 1 Seruway demonstrates the critical role of formal education in sustaining linguistic and cultural heritage in an increasingly globalized society.